Karakteristik Kepribadian Narapidana Kasus Pembunuhan Berencana Ditinjau dari Minnesota Multiphasic Personality Inventory-2 - Rahel Gloria Natalia Abel; Setyani Alfinuha (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Crime as premeditated murder is one of the main problems in Indonesia. The prevalence of murder cases tends to increase. Personality characteristics that play a role in the case of premeditated murder are unique. Prison convicts have varied and unique personality compared to people in general. A test uses to find out the personality traits that were needed to administer. Thus, the diagnosis and application of intervention were preciseness. The measuring instrument employed in this study was the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). This study aims to determine the psychopathological indications of convicted murder cases in MMPI-2. The sampling technique used purposive sampling with one participant planning murder who was serving a prison sentence of 20 years. The result is participants had a psychopathological predisposition to schizophrenia (84 = very high), paranoia (83 = very high), and hypomania (81 = very high). A prisoner with this kind of psychopathological predisposition tended to feel insecure, lonely, anxious, and depressed but sometimes also felt happy or have excessive energy. The participant also avoided social relations and did not want to involve emotions deeply. The results of MMPI-2 showed that the characteristics of schizophrenia, paranoid, hypomania might encourage someone to commit sadistic behavior such as serial killings